SMRT-mediated co-shuttling enables export of class IIa HDACs independent of their CaM kinase phosphorylation sites - Soriano, Francesc X (Blackwell Publishing Ltd, 2013)
The Class IIa histone deacetylases (HDAC)4 and HDAC5 play a role in neuronal survival and behavioral adaptation in the CNS. Phosphorylation at 2/3 N-terminal sites promote their nuclear export. We investigated whether non-canonical signaling routes to Class IIa HDAC export exist because of their association with the co-repressor Silencing Mediator Of Retinoic And Thyroid Hormone Receptors (SMRT). We found that, while HDAC5 and HDAC4 mutants lacking their N-terminal phosphorylation sites (HDAC4(MUT), HDAC5(MUT)) are constitutively nuclear, co-expression with SMRT renders them exportable by signals that trigger SMRT export, such as synaptic activity, HDAC inhibition, and Brain Derived Neurotrophic Factor (BDNF) signaling. We found that SMRT's repression domain 3 (RD3) is critical for co-shuttling of HDAC5(MUT), consistent with the role for this domain in Class IIa HDAC association. In the context of BDNF signaling, we found that HDAC5(WT), which was more cytoplasmic than HDAC5(MUT), accumulated in the nucleus after BDNF treatment. However, co-expression of SMRT blocked BDNF-induced HDAC5(WT) import in a RD3-dependent manner. In effect, SMRT-mediated HDAC5(WT) export was opposing the BDNF-induced HDAC5 nuclear accumulation observed in SMRT's absence. Thus, SMRT's presence may render Class IIa HDACs exportable by a wider range of signals than those which simply promote direct phosphorylation.